Calidad de servicio y satisfacción del cliente en la empresa Némesís Games, Iquitos 2024 - Gomez Iruyari, Lesly Marili (2025)
he research work entitled "Customer Satisfaction and Service Quality at Nemesis Games, Iquitos 2024" is dedicated to studying the connection between these two variables. In the first section, the background and theoretical foundations relevant to the study were explored. In the second section, the hypotheses were established and the variables to be analyzed were clarified. The third section details the methodological approach, which follows a quantitative, descriptive and non-experimental style. The study group is made up of 20 frequent consumers of the company. A 21-question form was used to collect data about the service and customer satisfaction. The consistency of the instrument was assessed using Cronbach's alpha coefficient, obtaining a value of 0.958, suggesting that the questionnaire is reliable. The data were analyzed using Microsoft Excel and the statistical program SPSS v26.